UPAYA MENINGKATKAN KEMAMPUAN BERHITUNG SISWA KELAS 1 SD MENGGUNAKAN MEDIA MANIPULATIF DENGAN PENDEKATAN BERDIFERENSIASI - Maria Ulfa; Sumianto; Dwi Viora; Muhammad Syahrul Rizal; Nasrul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve the ability to count math addition and subtraction material for grade 1 UPT SD Negeri 007 Bangkinang students. This study was motivated by the low counting ability of students in addition and subtraction material in grade 1 students totaling 24 students, 14 male students and 10 female students. This research is a class action research where the implementation is carried out in two cycles and each cycle consists of two meetings. Data collection techniques in this study used observation techniques, tests and documentation. Based on the results of data analysis, it can be seen that there is an increase in students' counting skills in addition and subtraction material. Before the action, the completeness of the results of students' counting skills was only 50% in the very poor category. In implementing cycle 1 meeting 1, the completeness of the results of students' numeracy skills reached 58% in the category of less. In cycle 1 meeting 2, the test results of students' numeracy skills reached 66% in the sufficient category. While in cycle 2 meeting 1, the results of the student counting skills test reached 75% in the good category. In cycle 2 meeting 2, the test results of students' counting skills reached 91% in the very good category. Thus it can be concluded that students' counting skills can be improved by using manipulative media with a differentiated approach.